Comprehensive assessment of performance and reliability of PERC, TOPCon and SHJ modules in desert climates - Maulid Kivambe (19344709) (2025)
Tunnel Oxide Passivated Contact (TOPCon) and Silicon Heterojunction (SHJ) solar cells are key technologies in the photovoltaic (PV) market, replacing Passivated Emitter and Rear Cell (PERC) technology which have dominated the market for the past decade. Despite the advancements and rapid market adoption, the performance and reliability of these technologies in the field remain inadequately understood. This study evaluates the performance and reliability of commercial PERC, TOPCon, and SHJ PV modules installed in Qatar’s desert climate for about three years. The modules were assessed indoors and outdoors to evaluate degradation over time, performance ratios and specific energy yield across seasons. During the study period, SHJ modules exhibited the highest degradation, with average Pmax decline of up to 8.73% relative. One TOPCon model showed notable degradation, while the other model demonstrated superior stability and the lowest overall degradation. PERC modules experienced significant degradation initially but showed a marked reduction in degradation after the first year, unlike SHJ and the TOPCon modules whose degradation rates persisted over time. Visual inspections revealed significant encapsulant delamination, occurring mostly in the first year in the SHJ modules. Ultraviolet Fluorescence imaging showed signs of severe encapsulant and edge-seal degradation in some of the SHJ and TOPCOn modules. These findings indicate potential for early failure. Performance ratios show that bifacial SHJ and TOPCon modules generally outperform PERC modules. However, a particular model of PERC module exhibited an exceptional performance in the field, suggesting the use of superior materials or manufacturing process. This study highlights the advantages and challenges of advanced PV technologies in harsh climatic conditions, providing valuable insights into their potential for large-scale deployment. Other Information Published in: Solar Energy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.solener.2025.113555